Analisis Bibliometrik Penerapan Media Flash Card Pada Materi Pendidikan Agama Islam Dengan Menggunakan Aplikasi VOSViewer dan Publish Or Perish (Tahun 2019-2024) - Nur Indah Sari; Santiani (PT. Intelek Cendikiawan Nusantara, 2024)
This study aims to analyze the development of publications related to the application of flash card media in Islamic religious education materials. The research method used in this study is Bibliometric analysis, which uses the VOSViewer application. Collecting Publication Data using the Publish or Perish application to obtain article data from Google Schoolar indexed journals. The results of this study show that there have been many research developments related to the application of flash card media since 2019-2024. This research has increased from 2019 to 2023 and decreased in 2024. This topic is often discussed in the keywords Medium, Media flash card, and Flash card, but the topic of flashcard media in Islamic religious education material is still little so that VOSviewer mapping is almost invisible